1990
DOI: 10.1007/bf00685720
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin in malignant mesothelioma: A phase II study of the cancer and leukemia Group B

Abstract: Carboplatin (400 mg/m2) was given at 28-day intervals to 41 patients with malignant mesothelioma. In all, 40 patients were eligible and evaluable for response. Partial responses were seen in 2 cases (5%); regression of evaluable disease, in 1 patient (2%); and stable disease, in 19 subjects (48%). A median of two doses of carboplatin per patient resulted in mild toxicity. Leukopenia (less than or equal to 2,000 cells/microliters) and thrombocytopenia (less than 100,000 cells/microliters) were seen in only 6% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Single-agent cisplatin resulted in a response rate of merely 14.3% and a median survival of 7.5 months (Zidar et al, 1988). Studies using the newer compound carboplatin resulted in similar response rates ranging between 6 and 16% (Mbidde et al, 1986;Raghavan et al, 1990;Vogelzang et al, 1990).…”
Section: Single-agent Chemotherapymentioning
confidence: 99%
“…Single-agent cisplatin resulted in a response rate of merely 14.3% and a median survival of 7.5 months (Zidar et al, 1988). Studies using the newer compound carboplatin resulted in similar response rates ranging between 6 and 16% (Mbidde et al, 1986;Raghavan et al, 1990;Vogelzang et al, 1990).…”
Section: Single-agent Chemotherapymentioning
confidence: 99%
“…Our combination regimen was chosen because carboplatin has single-agent activity against MPM. Carboplatin has a similar activity to cisplatin, but with milder toxicity, 7,18,19 whereas gemcitabine is active against various solid tumors and alleviates symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Virtually every class of chemotherapy has been tested, but few have shown consistent response rates greater than 20% [13]. Many multidrug trials, including four phase II and phase III studies by the Cancer and Leukemia Group B, have shown no clear improvement over single-agent chemotherapy [14,15]. Because systemic chemotherapy has had little effect on the progression of disease, intrapleural chemotherapy also has been evaluated in clinical trials [16,17].…”
Section: Opinion Statementmentioning
confidence: 98%